AAPM task group report 302: Surface‐guided radiotherapy. Issue 4 (15th March 2022) - Al‐Hallaq, Hania A.; Cerviño, Laura; Gutierrez, Alonso N.; Havnen‐Smith, Amanda; Higgins, Susan A.; Kügele, Malin; Padilla, Laura; Pawlicki, Todd; Remmes, Nicholas; Smith, Koren; Tang, Xiaoli; Tomé, Wolfgang A.
Abstract: The clinical use of surface imaging has increased dramatically, with demonstrated utility for initial patient positioning, real‐time motion monitoring, and beam gating in a variety of anatomical sites. The Therapy Physics Subcommittee and the Imaging for Treatment Verification Working Group of the American Association of Physicists in Medicine commissioned Task Group 302 to review the current clinical uses of surface imaging and emerging clinical applications. The specific charge of this task group was to provide technical guidelines for clinical indications of use for general positioning, breast deep‐inspiration breath hold treatment, and frameless stereotactic radiosurgery. Additionally, the task group was charged with providing commissioning and on‐going quality assurance (QA) requirements for surface‐guided radiation therapy (SGRT) as part of a comprehensive QA program including risk assessment. Workflow considerations for other anatomic sites and for computed tomography simulation, including motion management, are also discussed. Finally, developing clinical applications, such as stereotactic body radiotherapy (SBRT) or proton radiotherapy, are presented. The recommendations made in this report, which are summarized at the end of the report, are applicable to all video‐based SGRT systems available at the time of writing.